Negative electrode sheet and electrochemical device

By designing the double -layer structure containing phase -changing particle layers on the negative poles of lithium ion batteries, the problem of low efficiency and safety hazards during the first charging process of lithium ion batteries is solved, and higher energy density and safety performance are achieved.

CN114583109BActive Publication Date: 2025-01-24NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210214164.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-01-24
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

During the first charging process of existing lithium-ion batteries, due to the formation of SEI film and the irreversible consumption of active lithium, the Coulomb efficiency is low, the capacity and energy density are reduced, and the side reaction of metal lithium during the pre-replenishment process leads to the temperature rise of the electrode sheet. High, poses safety risks.

Method used

Designed a new type of negative pole, including a stream, a silicon -containing negative membrane layer, and a phase variable layer. The phase transformer layer consists of phase -changing particles with a nuclear shell structure. These phase variable particles Absorb heat and reduce the temperature rise.

Benefits of technology

It effectively reduces the temperature rise of the pole piece during the lithium replenishment process, improves the rate performance and safety performance of lithium-ion batteries, reduces the risk of short circuit of the positive and negative electrodes, and improves the capacity and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114583109B_ABST
    Figure CN114583109B_ABST
Patent Text Reader

Abstract

The present invention provides a novel negative electrode plate, the negative electrode plate comprises a current collector, a silicon-containing negative electrode film layer on the current collector, a phase change layer on the silicon-containing negative electrode film layer, the phase change layer comprises phase change particles, and the phase change particles have a core-shell structure. The present invention also provides a method for preparing a negative electrode plate, an electrochemical device including the negative electrode plate, and an electronic device including the electrochemical device. The negative electrode plate of the present invention improves the performance and safety problems caused by the pre-lithium supplementation process on the surface of the negative electrode plate in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemistry, in particular to a negative electrode plate and an electrochemical device, and also to an electronic device comprising the electrochemical device. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, electric vehicles, home energy storage and other fields. In recent years, with the rapid development of 5G communications, new energy vehicles, etc., the market has put forward higher demands on the endurance of lithium-ion batteries, and the development of high-energy density batteries is imperative. During the first charging process of lithium-ion batteries, the organic electrolyte is reduced and decomposed on the surface of the negative electrode material to form a solid electrolyte interface (SEI), and at the same time, a large amount of active lithium from the positive electrode is irreversibly consumed, resulting in a low initial coulombic efficiency of the whole battery, reducing the capacity and energy density of the lithium-ion battery. The first irreversible lithium loss of graphite materials is 5% to 10%, while the first irreversible lithium consumption of silicon materials is as high as 15% to 35%. In order to overcome the problem of active lithium loss caused by the formation of SEI film during the first charge and discharge of the battery, it is usually used to supplement lithium in advance by supplementing the lithium-rich layer on the negative electrode side to supplement the active lithium in the battery and improve the battery's first efficiency, energy density and cycle performance. The existing commercial pre-replenishment of lithium is to roll metal lithium foil, lithium powder and lithium strips onto the surface of the negative electrode after cold coating by physical methods. Summary of the invention

[0003] Since the metallic lithium used in pre-replenishment is extremely active, it can react with oxygen, nitrogen and carbon dioxide in the air. It can also react with silicon-oxygen materials to form lithium silicates. These chemical reactions will cause a large amount of heat to be released, and the temperature of the electrode will rise too much, causing damage to the active substances and degradation of the lithium-ion battery performance. In severe cases, it can cause safety accidents such as smoke and fire.

[0004] In order to control the temperature rise of the electrode during the lithium replenishment process, it is necessary to reduce the winding length of the electrode during the lithium replenishment operation, for example, every 1540.25mm 2 When the amount of lithium supplemented on the electrode is >6mg, the winding length needs to be <60m to avoid heat accumulation; during the winding process, a layer of recyclable insulation material will be rolled in between the electrode pieces at the same time; the electrode pieces after winding need to be left in the cold air box for more than 2.0 hours, and the cold air box can only be taken out after the temperature drops to room temperature. Because there is a layer of insulation material in the winding process and the winding length is very short, the electrode pieces after lithium supplementation cannot be automatically wound on the machine and can only be operated manually, which seriously affects production efficiency; the electrode pieces need to be cooled by cold air boxes, and the expensive lithium supplementation drying room also needs to add large cold air boxes, which increases equipment costs and operating costs, and affects the production rate, which is not conducive to mass production operations. In addition, since these temperature control methods are greatly interfered by human operations, etc., the temperature rise control is unstable, which is not conducive to the stable control of lithium-ion battery performance.

[0005] Therefore, there is an urgent need to provide a new type of negative electrode plate design to improve the problems of large amounts of heat generated by metal lithium foil, lithium bars and lithium powder during the pre-lithium replenishment process on the surface of the negative electrode plate, deterioration of lithium-ion battery performance caused by excessive temperature rise of the plate, and safety risks of lithium replenishment.

[0006] In view of this, an object of the present invention is to provide a new type of negative electrode plate, a method for preparing the negative electrode plate, an electrochemical device including the negative electrode plate, and an electronic device including the electrochemical device. The negative electrode plate improves the performance and safety problems caused by the pre-lithium replenishment process on the surface of the negative electrode plate in the prior art.

[0007] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a negative electrode plate, which includes a current collector, a silicon-containing negative electrode film layer on the current collector, and a phase change layer on the silicon-containing negative electrode film layer, wherein the phase change layer includes phase change particles, and the phase change particles have a core-shell structure.

[0008] In some embodiments, the core in the core-shell structure includes a phase change material.

[0009] In some embodiments, the phase change particles have a Dv50 of from 1 μm to 10 μm.

[0010] In some embodiments, the phase change enthalpy of the phase change material is from 100 to 220 J / g.

[0011] In some embodiments, the phase change material has a phase transition temperature ranging from 40°C to 60°C.

[0012] In some embodiments, the phase change material includes at least one of a hydrocarbon compound, a fatty acid compound, an alcohol compound, and an ester compound.

[0013] In some embodiments, the hydrocarbon compound includes at least one of an aliphatic hydrocarbon compound having 16 to 100 carbon atoms, an aromatic hydrocarbon compound having 18 to 120 carbon atoms, an alicyclic hydrocarbon compound having 16 to 100 carbon atoms, and paraffin; or the fatty acid compound includes at least one of lauric acid, tetradecanoic acid, pentadecanoic acid, stearic acid, or eicosanoic acid;

[0014] Or, the alcohol compound includes at least one of dodecanol, tetradecanol, hexadecanol or erythritol;

[0015] Alternatively, the ester compound includes at least one of cellulose laurate or cetyl stearate.

[0016] In some embodiments, the shell layer of the phase change particle includes an inorganic material, and the inorganic material includes at least one of tetratitanium fiber, barium titanate, zirconium oxide, aluminum oxide, titanium oxide, silicon oxide, lithium titanate, boron trioxide, and magnesium oxide.

[0017] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising: (1) forming a silicon-containing negative electrode film layer on a current collector; and (2) forming a phase change particle layer on the silicon-containing negative electrode film layer.

[0018] In some embodiments, the method for preparing a negative electrode sheet of the present invention includes (3) performing lithium supplementation.

[0019] In a third aspect of the present invention, an electrochemical device comprising the negative electrode sheet of the present invention is provided.

[0020] In a fourth aspect of the present invention, an electronic device comprising the electrochemical device of the present invention is provided.

[0021] It can be seen from the above technical solution that the negative electrode plate of the present invention includes a phase change layer containing phase change particles. During the lithium replenishment process, when the temperature of the negative electrode plate rises, the phase change material inside the phase change particles changes from solid to liquid, quickly absorbs heat, and reduces the risk of fire during the lithium replenishment process. The heat absorbed by the phase change material can be slowly released in the subsequent process. This heat is conducive to accelerating the solid phase diffusion of metallic lithium into the negative electrode plate, improving the rate performance of the lithium-ion battery, and at the same time reducing the risk of positive and negative short circuits caused by residual lithium metal on the surface of the plate, thereby improving the safety performance of the lithium-ion battery. Therefore, the new negative electrode plate of the present invention improves the performance and safety problems caused by the pre-lithium replenishment process on the surface of the negative electrode plate in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the implementation scheme of the present application, the drawings required for use in the implementation scheme and / or examples will be briefly introduced below. Obviously, the drawings described below can help to better understand the technical solution of the present invention, but are not intended to limit the scope of the present invention.

[0023] Figure 1 is a schematic top view showing the distribution of phase change particles on the surface of a pole piece in one embodiment of the present invention;

[0024] Figure 2 is a schematic side view showing the distribution of phase change particles on the surface of a pole piece in one embodiment of the present invention; and

[0025] Figure 3 is a schematic diagram showing the composition of phase change particles in one embodiment of the present invention. DETAILED DESCRIPTION

[0026] In order to make those skilled in the art better understand the embodiments of the present invention, the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field should fall within the scope of protection defined by the claims attached to the present invention.

[0027] It should be noted that, in the embodiments of the present invention, a lithium ion battery is used as an example of an electrochemical device to illustrate the present invention, but the electrochemical device of the present invention is not limited to a lithium ion battery.

[0028] During the first charging process of lithium-ion batteries, the organic electrolyte is reduced and decomposed on the surface of the negative electrode material to form a solid electrolyte interface (SEI), and at the same time, a large amount of active lithium from the positive electrode is irreversibly consumed, resulting in a low initial coulombic efficiency of the entire battery, which reduces the capacity and energy density of the lithium-ion battery. In order to overcome the problem of active lithium lost due to the formation of the SEI film during the first charge and discharge of the battery, it is usually used to pre-supplement lithium by supplementing the lithium-rich layer on the negative electrode side to supplement the active lithium in the battery and improve the battery's initial efficiency, energy density and cycle performance. However, since the metal lithium used in the pre-supplement lithium is extremely active, it can react with oxygen, nitrogen and carbon dioxide in the air, and also react with silicon oxide materials to form lithium silicates. These chemical reactions will all lead to a large amount of heat release, excessive temperature rise of the pole piece, damage to the active material, and degradation of the lithium-ion battery performance. In severe cases, it will cause safety accidents such as smoking and fire. In addition, the current commercial pre-supplement lithium method is to roll metal lithium foil, lithium powder and lithium strips onto the surface of the negative electrode after cold pressing by physical methods. In the process of pre-lithium replenishment, the production efficiency is low due to the complexity of the process and the fact that it includes steps that can only be operated manually. At the same time, the process also has disadvantages such as increased equipment cost and operating cost, and the temperature control method is easily disturbed, resulting in unstable temperature rise control.

[0029] In order to improve the problems of large amount of heat generated by metal lithium foil, lithium bars and lithium powder during the pre-lithium replenishment process on the surface of the negative electrode plate, deterioration of lithium-ion battery performance caused by excessive temperature rise of the plate, and safety risks of lithium replenishment, the present invention provides a new type of negative electrode plate.

[0030] The negative electrode plate of the present invention comprises a current collector, a silicon-containing negative electrode film layer on the current collector, and a phase change layer on the silicon-containing negative electrode film layer. The phase change particle layer comprises phase change particles having a core-shell structure. Figure 1 and 2The top view and side view of the negative electrode sheet structure in some embodiments of the present invention are shown. In some embodiments of the present invention, the current collector of the present invention has a thickness range of 4 μm to 20 μm, the silicon-containing negative electrode film layer has a thickness range of 5 μm to 60 μm, and the phase change layer has a thickness range of 1 μm to 10 μm.

[0031] When used in the present invention, the phase change particles have a core-shell structure, and are preferably microspheres having a core-shell structure. Figure 3 A schematic diagram of the composition of phase change particles in some embodiments of the present invention is shown. The particle size (Dv50) of the phase change particles will affect both its ability to reduce the temperature rise of the pole piece and the loss of the volume energy density of the lithium-ion battery. When the particle size is small, less heat is absorbed, which is not conducive to reducing the temperature rise of the pole piece, but the effect on the energy density is small. When the particle size is large, the temperature rise of the pole piece is better controlled, but it may cause a large loss of energy density. Therefore, a suitable phase change particle size will help to realize the present invention. In the present invention, the phase change particles have a particle size Dv50 in the range of 1μm to 10μm, preferably 1μm to 7μm, more preferably 1μm to 5μm, and most preferably 1μm to 3μm.

[0032] Phase change particles include a core made of phase change material (PCM). When used in this article, the term "phase change material" refers to a material that changes the state of matter and can provide latent heat under constant temperature. The phase change material that can be used in the present invention includes at least one selected from the group consisting of hydrocarbon compounds, fatty acid compounds, alcohol compounds and ester compounds. When used in this article, hydrocarbon compounds are mainly paraffin-like straight-chain hydrocarbon materials, such as C16 or C18 even-numbered carbon atom paraffin or its long-branched modified paraffin.

[0033] The fatty acid compound includes at least one selected from the group consisting of lauric acid, tetradecanoic acid, pentadecanoic acid, stearic acid or eicosanoic acid, such as a lauric acid system, a capric acid and lauric acid mixed system, and the like.

[0034] The alcohol compound includes at least one selected from the group consisting of dodecanol, tetradecanol, hexadecanol or erythritol, such as pentaerythritol, trimethylolethane, neopentyl glycol, trimethylolaminomethane and the like.

[0035] The ester compound includes at least one selected from the group consisting of cellulose laurate or cetyl stearate, such as stearic acid-n-butyl alcohol ester, stearic acid-isopropyl alcohol ester, and the like.

[0036] In the present invention, the phase change enthalpy of the phase change material is in the range of 100 J / g to 220 J / g. Further, the phase change enthalpy of the phase change material may be in the range of 120 J / g to 180 J / g, 160 J / g to 200 J / g, 180 J / g to 220 J / g, and 200 J / g to 220 J / g.

[0037] In the present invention, the phase transition temperature of the phase change material ranges from 40°C to 60°C. Further, the phase transition temperature of the phase change material may range from 40°C to 50°C, 45°C to 55°C, or 50°C to 60°C.

[0038] The phase change particles include a shell covering and encapsulating the inner core. The shell that can be used in the present invention is mainly an inorganic material, preferably mainly an inorganic ceramic material, so as to isolate the phase change material from the external environment and improve the electrolyte permeability of the electrode surface area.

[0039] Specifically, the shell material is mainly an inorganic ceramic material that can accelerate the transfer of lithium ions in the electrolyte. In some embodiments, the inorganic ceramic material includes at least one selected from the group consisting of tetratitanium fiber, barium titanate, zirconium oxide, aluminum oxide, titanium oxide, silicon oxide, lithium titanate, boron trioxide, and magnesium oxide, or a mixture of more. In some embodiments, the inorganic ceramic material is silicon oxide.

[0040] In some embodiments, the preparation method of the phase change particles of the present invention is as follows: the phase change material constituting the core and the precursor material constituting the shell are mixed and stirred evenly; the mixture of the phase change material and the shell precursor material is added to the emulsifier solution, and the phase change material fine emulsion is obtained by high-speed homogenizer treatment; the inorganic acid aqueous solution is slowly added to the above phase change material fine emulsion, and a solid-liquid mixture is obtained by stirring and aging; the obtained solid-liquid mixture is centrifuged, washed, and dried to obtain the phase change particles of the present invention. Among them, the size of the phase change particles can be achieved by adjusting the size of the phase change material fine emulsion droplets.

[0041] In some embodiments, the phase change material and the inorganic material are mixed in a ratio of 3:1 to 1:3, preferably in a ratio of 2:1 to 1:2, and more preferably in a ratio of 1:1. The mixing conditions include a stirring temperature of 40°C to 60°C, preferably 45°C to 55°C; a stirring time of 0.5 to 3 hours, preferably 0.5 to 2 hours, and more preferably 0.5 to 1.5 hours.

[0042] In some embodiments, the emulsifier may be a common emulsifier in the art, such as sodium dodecylbenzene sulfonate, which is dissolved in formamide to obtain an emulsifier solution that can be used in the present invention.

[0043] In some embodiments, the inorganic acid may be a common inorganic acid in the art, such as a hydrochloric acid aqueous solution with a concentration of 1.0 mol / L to 2.0 mol / L. The reaction conditions used in the above process may be determined by those skilled in the art.

[0044] The present invention also provides a method for preparing the above-mentioned negative electrode sheet. The preparation method can form a double-layer structure on the surface of the current collector, namely, a silicon-containing negative electrode film layer on the current collector and a phase change particle layer on the silicon-containing negative electrode film layer, thereby obtaining the negative electrode sheet of the present invention. The coating mass range per unit area of ​​the silicon negative electrode film layer is: 1 mg / cm 2 Up to 10mg / cm 2 , the coating mass range of the phase change particle layer is: 0.3mg / cm 2 Up to 3mg / cm 2 .

[0045] The negative electrode sheet preparation method of the present invention can adopt a double-layer continuous coating method. Specifically, two extrusion heads stacked up and down are used, and the lower extrusion head can coat the silicon-containing negative electrode film slurry on the surface of the current collector, while the phase change particle slurry flowing out of the upper extrusion head can be distributed on the surface of the silicon-containing negative electrode film slurry. The current collector composed of copper foil is unwound on one side and rolled up on the other side. The part coated with the slurry directly passes through a large oven, and the water in the slurry on the surface of the current collector is completely volatilized by adjusting the conveying speed and the oven temperature, thereby forming the above-mentioned double-layer structure on the surface of the current collector.

[0046] The negative electrode sheet preparation method of the present invention can also adopt a double-layer coating method. Specifically, firstly, a silicon-containing negative electrode film slurry is coated on the surface of the current collector, and then a drying step is performed to form a silicon-containing negative electrode film layer; then, a phase change particle slurry is coated on the silicon-containing negative electrode film layer, and finally a drying step is performed to form the above-mentioned double-layer structure on the surface of the current collector.

[0047] The silicon-containing negative electrode film slurry used in the present invention includes 85 to 99 parts by weight of negative electrode active material, 0.1 to 10 parts by weight of conductive agent and 0.1 to 10 parts by weight of binder. In some embodiments, the negative electrode active material is a mixture of silicon and other active materials such as graphite, hard carbon, lithium titanate, etc., wherein the mass proportion of silicon is 0.1 to 100%; the silicon includes one or more composite materials of pure silicon, silicon oxide, silicon carbon, etc. In some embodiments, the conductive agent is a mixture of one or more of carbon nanotubes, Super P, graphene, carbon fiber, etc.; the binder is one or more of polyacrylate, styrene-butadiene rubber, nitrile rubber, polyimide, polyamide-imide, etc.

[0048] The phase change particle slurry used in the present invention includes 90 to 99 parts by weight of phase change particles, 1 to 3 parts by weight of conductive ion polymer binder, and 0.05 to 0.5 parts by weight of conductive agent. In some embodiments, the conductive agent is a mixture of one or more of carbon nanotubes, SuperP, graphene, carbon fiber, etc.; the binder is one or more of lithium polyacrylate, styrene-butadiene rubber, nitrile rubber, polyimide, polyamide-imide, etc.

[0049] The negative electrode sheet preparation method of the present invention further includes a lithium supplementation step. The lithium supplementation step can be a known lithium supplementation process, for example, including but not limited to rolling metal lithium foil, lithium powder and lithium bar on the surface of the negative electrode sheet obtained by the preparation method of the present invention by a physical method.

[0050] The present invention also provides an electrochemical device comprising the negative electrode sheet. The electrochemical device of the present invention is applicable to electronic devices in various fields.

[0051] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any use known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium ion capacitors, etc.

[0052] The present invention also provides an electronic device comprising the electrochemical device.

[0053] Example

[0054] The following uses a lithium-ion battery as an electrochemical device to specifically describe the embodiments and comparative examples of the present invention. Through these embodiments and comparative examples, it is more convenient to see the significant advantages of the negative electrode sheet of the present invention over the prior art. It should be understood that the following embodiments and comparative examples are only used to better illustrate the technical solution of the present invention, and are not intended to limit the present invention.

[0055] Preparation of lithium-ion batteries

[0056] 1.1 Preparation of positive electrode

[0057] Lithium cobalt oxide, acetylene black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone (NMP) solution at a weight ratio of 94:3:3 to form a positive electrode slurry. Aluminum foil is used as a positive electrode current collector, and the positive electrode slurry is coated on the positive electrode current collector. After drying, cold pressing and cutting procedures, the positive electrode is obtained.

[0058] 1.2 Preparation of isolation membrane

[0059] Polyvinylidene fluoride is dissolved in water and formed into a uniform slurry through mechanical stirring. The slurry is coated on both sides of a porous substrate (polyethylene) that has been coated with a ceramic coating on both sides, and then dried to form an isolation film.

[0060] 1.3 Preparation of electrolyte

[0061] In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.

[0062] 1.4 Preparation of negative electrode and battery cell

[0063] Comparative Example 1

[0064] The negative electrode active material is a mixture of 60% silicon material and 40% graphite. The mixed negative electrode active material, styrene-butadiene rubber and carbon nanotube conductive agent are dispersed in deionized water at a ratio of 97:2.5:0.5 to prepare the negative electrode membrane slurry. It is coated on an 8μm copper foil current collector, and the negative electrode plate is obtained through drying, cold pressing and cutting procedures. The negative electrode plate is baked in a vacuum oven at 85°C for 24 hours until the water content of the plate is less than 300ppm, and then a layer of lithium foil is compounded on the negative electrode plate by rolling, with a thickness of 1cm 2 The mass of lithium foil on the negative electrode is 0.52 mg. The aluminum tab is welded to the positive electrode, the nickel tab is welded to the negative electrode, and the positive and negative electrode tabs welded with the tabs are separated by an isolation film and wound into a rectangular shape to make a battery cell.

[0065] Example 1

[0066] An uncut negative electrode sheet was prepared according to the method of Comparative Example 1, and then a phase change particle layer was coated on the uncut negative electrode sheet. The phase change particles were prepared by ourselves, and the preparation method was as follows: In a beaker, 20g of paraffin wax and 20g of ethyl orthosilicate were mixed and stirred at 50°C for 1 hour. In a three-necked flask, 3g of sodium dodecylbenzene sulfonate was dissolved in 200mL of formamide, stirred for 30 minutes to obtain an emulsifier solution, and then the paraffin ear ethyl orthosilicate mixture was added to the three-necked flask, and a paraffin fine emulsion was prepared by a high-speed homogenizer for 3 hours, and then a hydrochloric acid aqueous solution (200mL, 1.8mol / L) was slowly added to the prepared emulsion, and stirred at 100rpm for 4 hours, and aged at 50°C for 18 hours. The obtained solid-liquid mixture was centrifuged, washed, and dried to obtain a SiO2 shell and a paraffin core, and a phase change particle with a particle size of 1μm was obtained by Dv50. The obtained phase change particles were dispersed in deionized water with styrene-butadiene rubber and carbon nanotubes in a ratio of 98:1.8:0.2, and fully stirred to obtain a phase change particle slurry. The phase change particle slurry was coated on the cold-pressed negative electrode sheet, and the negative electrode sheet coated with phase change particles on the surface was obtained after drying, cold pressing, and cutting procedures. Subsequently, the pre-lithium replenishment baking (the water content of the electrode is less than 300 ppm) and lithium replenishment are performed according to the method of Comparative Example 1. The aluminum electrode tab is welded to the positive electrode tab, the nickel electrode tab is welded to the negative electrode tab, and the positive and negative electrode tabs welded with the electrode tabs are separated by a separator, and wound into a rectangular parallelepiped shape to make a battery cell.

[0067] Embodiment 2-5

[0068] The negative electrode sheet was manufactured according to the method of Example 1, except that the particle size of the phase change particles was 2, 3, 4, and 5 μm, respectively. In addition, the slurry ratio of the phase change particles, styrene-butadiene rubber, and carbon nanotubes, the coating process on the negative electrode sheet, and the subsequent cell preparation process in Examples 2-5 were the same as those in Example 1.

[0069] 1.5 Preparation of lithium-ion batteries

[0070] As described above, the negative electrode plates of Comparative Example 1 and Examples 1-5 after lithium supplementation were separated by a separator to form a battery cell. The battery cell was placed in a folded aluminum-plastic film, with the protruding end of the battery cell pole ear as the top. One side of the aluminum-plastic film was then hot-pressed and sealed, leaving one side for baking to remove excess moisture from the electrode plate, and then the electrolyte was injected, formed, and degassed, and the remaining side of the aluminum-plastic film was hot-pressed and sealed to obtain a lithium-ion battery. The final size was a soft-pack lithium-ion secondary battery with a thickness of about 4 mm, a width of 35 mm, and a length of 80 mm.

[0071] Performance Testing

[0072] 2.1 Calculation Phase change particles can reduce the temperature of the electrode.

[0073] The phase change particles can be set to be closely connected and laid flat on the surface of the active material layer in a single layer; the internal phase change material has a density of 0.9g / cm 3 The specific heat of silicon and graphite are 700 J / (Kg*℃) and 710 J / (Kg*℃) respectively, and the specific heat of the mixture is between the two.

[0074] On the negative electrode plate per unit area, the phase change particles can reduce the temperature rise by ΔT=Q / (CW*c), where ΔT is the temperature rise (℃); Q is the heat absorption of the phase change material (J); CW is the coating mass of the negative electrode active material layer per unit area (Kg); c is the specific heat capacity of the mixed active material (J / (Kg*℃)). The heat absorption of the phase change material is Q=M*H, where M is the mass of the phase change particle size per unit area of ​​the negative electrode plate (Kg), and H is the phase change enthalpy of the phase change material (J / (Kg*℃)). On the negative electrode plate per unit area, the relationship between the mass of a single layer of phase change material and the particle size of the phase change material is: M=4 / 3*π*r 3 *ρ, where π is the circumference of a circle (3.14); r is the particle size of the phase change material (m); ρ is the density of the phase change material (Kg / m 3 ).

[0075] 2.2 Ionic resistance of negative electrode after lithium supplementation

[0076] The negative electrode pieces after lithium supplementation are taken and assembled into a symmetrical battery. The EIS spectrum is obtained through EIS analysis technology, and then the measured EIS impedance spectrum is fitted through Z-view, and the pore fluid resistance Rion is calculated by the software.

[0077] 2.3 Lithium-ion battery energy density

[0078] The lithium-ion battery after shipment is charged to 4.45V at a constant current of 0.2C, and then charged to 0.025C at a constant voltage to complete the full charge of the lithium-ion battery; then, it is discharged at a constant current of 0.2C until the voltage of the lithium-ion battery drops to 3.0V. During the discharge process, the total capacity released is recorded as C, the actual thickness of the lithium-ion battery is measured, and the actual volume of the lithium-ion battery V is calculated, ED = C / V;

[0079] 2.4 Battery self-discharge test (K value test)

[0080] The lithium-ion battery in the 50% SOC state is placed at 45°C for 24 hours, and then placed at 25°C for another 24 hours. A semi-automatic voltage internal resistance tester (OCV machine) is used to test the open circuit voltage at this time, which is recorded as OCV1. The lithium-ion battery is placed at 25°C for another 48 hours, and then the open circuit voltage is tested, which is recorded as OCV2. The K value is calculated as (OCV2-OCV1) / 48, (mV / h).

[0081] 2.5 Maximum non-lithium deposition rate

[0082] For lithium-ion batteries that have been formed and shipped, the charge rate is set to 1C, the discharge rate is 0.5C, and the cycle is repeated 10 times. When the lithium-ion battery is fully charged, the lithium-ion battery is removed and disassembled to determine whether lithium is deposited on the negative electrode surface. If lithium deposition does not occur, the charge rate is increased by 0.1C (1.1C, 1.2C, 1.3C, 1.4C) and the lithium deposition test is continued until lithium deposition occurs on the negative electrode interface. The charge rate at this time is recorded as the maximum rate without lithium deposition.

[0083] 2.6 Cycle Test

[0084] The lithium-ion battery was charged at a constant current of 0.7C to a full charge voltage of 4.45V, charged at a constant voltage of 0.025C, and then fully discharged at 0.5C to 3.0V as a charge and discharge cycle. The capacity retention rate of the lithium-ion battery after 800 cycles was recorded.

[0085] The data obtained from the above tests are summarized in Table 1.

[0086] Table 1 Data summary of each comparative example and embodiment

[0087]

[0088] The following is an analysis of the test conclusions based on the test results of the comparative example and each experimental example in Table 1 above, as follows:

[0089] Comparative Example 1 and Example 1 show that when the phase change particles with a particle size of 1 μm are coated on the negative electrode plate and then lithium is replenished, the phase change particles can reduce the temperature of the negative electrode plate by 26°C after lithium replenishment, significantly reducing the peak temperature of the plate after lithium replenishment. Due to the addition of a 1 μm phase change material layer on the surface of the negative electrode, the thickness of the lithium-ion battery increases, the volume energy density of the lithium-ion battery decreases from 852Wh / L to 849Wh / L, and the ED loss is small (about 0.3%). The capacity retention rate increases by 2.6% after 800cls. The reason is that the use of phase change particles to control the temperature rise of lithium replenishment and reduce the side reactions of lithium metal and air can improve the lithium replenishment effect and increase the amount of active lithium in the lithium-ion battery. In addition, the heat absorbed by the phase change material will be released slowly. The released heat is conducive to the solid-phase diffusion of lithium metal into the interior of the electrode, reducing residual lithium on the surface and improving the K value to 0.06 (the K value is the reduction value of the open circuit voltage of the battery per unit time. The larger the K value, the faster the open circuit voltage drops and the more serious the battery self-discharge problem. The K value is generally required to be less than 0.08). At the same time, it avoids excessive enrichment of lithium metal and lithium replenishment by-products on the surface of the negative electrode, improves the pore distribution of the negative electrode, reduces the electrode ion resistance from 53mΩ to 35.5mΩ, and increases the maximum non-lithium precipitation rate by 0.2C, improving the charging performance.

[0090] By comparing Examples 1-5, it can be found that as the size of the phase change particles increases, the phase change particles can reduce the temperature of the pole piece after lithium replenishment, but at the same time the ED loss is greater. When the particle size is ≥4μm, the ED loss is as high as 1.7%, and the loss is unacceptable. From the ED point of view, the phase change particle size is preferably 1μm to 3μm. Measuring the temperature rise of the pole piece after lithium replenishment in the comparative example, it can be seen that the peak temperature of the pole piece is about 72°C. From Examples 1, 2, and 3, it can be seen that when the phase change particle sizes are 1μm, 2μm, and 3μm, respectively, the phase change particles can reduce the pole piece temperature by 26°C, 53°C, and 79°C. Then within this particle size range, the temperature of the negative electrode after lithium replenishment can be reduced to below 60°C (safe temperature). In addition, when the particle size of the phase change particles increases, the ionic resistance of the lithium-supplemented electrode first decreases and then increases, and the maximum lithium-free times first increases and then decreases, with an inflection point appearing at a particle size of 3μm. This indicates that when the particle size is in the range of 1μm to 3μm, the solid-phase diffusion of lithium metal by the phase change particles gradually improves, the diffusion impedance of the electrolyte decreases, and better performance can be obtained.

[0091] In summary, the present invention forms a double-layer structure of a silicon-containing negative electrode film layer and a phase change particle layer on the current collector, thereby obtaining a negative electrode plate, which reduces the temperature rise of the plate during the pre-lithium replenishment process and significantly improves the performance and safety of lithium-ion batteries. After considering the specification and practicing the invention disclosed herein, those skilled in the art will easily think of other embodiments of the present application. This application is intended to cover any variations, uses or adaptive changes of the present disclosure, which follow the general principles of the present disclosure and include common knowledge or customary technical means in the technical field that are not disclosed in the present disclosure. The specification, implementation scheme and examples are to be regarded as exemplary only, and the true scope and spirit of the present application are indicated by the appended claims.

Claims

1. A negative electrode sheet, comprising a current collector, a silicon-containing negative electrode film layer on the current collector, and a phase change layer on the silicon-containing negative electrode film layer, wherein the phase change layer comprises phase change particles, the phase change particles have a core-shell structure, the core in the core-shell structure comprises a phase change material, the shell layer of the phase change particles comprises an inorganic material, the inorganic material comprises at least one of tetratitanium fiber, barium titanate, zirconium oxide, aluminum oxide, titanium oxide, silicon oxide, lithium titanate, boron trioxide, and magnesium oxide, the phase change material comprises at least one of a hydrocarbon compound, a fatty acid compound, an alcohol compound, and an ester compound, wherein: The hydrocarbon compound includes at least one of an aliphatic hydrocarbon compound having 16 to 100 carbon atoms, an aromatic hydrocarbon compound having 18 to 120 carbon atoms, and an alicyclic hydrocarbon compound having 16 to 100 carbon atoms; The Dv50 of the phase change particles is 2 μm to 3 μm; The phase change enthalpy of the phase change material is 120 J / g to 180 J / g; The phase change temperature range of the phase change material is 40°C to 60°C; The coating mass per unit area of ​​the silicon-containing negative electrode film layer is in the range of 1 mg / cm 2 Up to 10mg / cm 2 ; The coating mass per unit area of ​​the phase change layer is in the range of 0.3 mg / cm 2 Up to 3mg / cm 2 .

2. The negative electrode sheet according to claim 1, wherein: The phase change temperature of the phase change material ranges from 45°C to 55°C.

3. The negative electrode sheet according to claim 1, wherein: The fatty acid compound includes at least one of lauric acid, tetradecanoic acid, pentadecanoic acid, stearic acid or eicosanoic acid; Or, the alcohol compound includes at least one of dodecanol, tetradecanol, hexadecanol or erythritol; Alternatively, the ester compound includes at least one of cellulose laurate or cetyl stearate.

4. An electrochemical device comprising the negative electrode sheet according to any one of claims 1 to 3.

5. An electronic device comprising the electrochemical device according to claim 4.

Citation Information

Patent Citations

  • Phase change temperature control type electrode, preparation method thereof and lithium ion battery

    CN111430709A

  • Composite ceramic particles as well as preparation method and application thereof

    CN113278310A

  • Negative pole piece, lithium ion battery and preparation method and application of negative pole piece

    CN114023923A